Toying With Line Extensions to Generate Revenues: Have the Big Pharmas Lost Their Way? - Basu, Shravani (2009)
The traditional heavyweights or big pharmas of the modern pharmaceutical industry are facing unprecedented challenges, primarily, in the form of drying product pipelines, expiry of patents of blockbuster drugs and swiftly declining margins on existing products. While service provision for revenue generation was the topic under investigation in the preceding project with the Established Business Unit division of Pfizer, the current report is an analysis of the industry itself, and dwells upon the environment, structure, products and fundamental motivations shaping this sector, and thereby, making it unique from other manufacturing sectors.